COMPARATIVE FREE RADICAL SCAVENGING ACTIVITY OF ANGIOTENSIN RECEPTOR BLOCKERS - ANANDPRIYA V.V.M; DARLING CHELLATHAI DAVID (International Journal of Pharma and Bio Sciences, 2016)
Angiotensin receptor blockers (ARBs) are used in various disease conditions such as hypertension, heart failure and diabetic nephropathy. Telmisartan, Valsartan are potent ARBs and specific competitive antagonist of angiotensin AT1 receptors. Oxidative stress has a vital role in the pathogenesis of hypertension, diabetes mellitus, and cardiac failures. In this study, the antioxidant potential of Telmisartan and Valsartan was evaluated and compared using DPPH assay. It was found out that both these drugs have antioxidant properties and Valsartan has better antioxidant property than Telmisartan. In conclusion, the antioxidant property of the above ARBs could be beneficial in preventing complications in various disease conditions due to oxidative damage.